If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + 1 = 5h + -3h + 2 Reorder the terms: 1 + h = 5h + -3h + 2 Reorder the terms: 1 + h = 2 + 5h + -3h Combine like terms: 5h + -3h = 2h 1 + h = 2 + 2h Solving 1 + h = 2 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. 1 + h + -2h = 2 + 2h + -2h Combine like terms: h + -2h = -1h 1 + -1h = 2 + 2h + -2h Combine like terms: 2h + -2h = 0 1 + -1h = 2 + 0 1 + -1h = 2 Add '-1' to each side of the equation. 1 + -1 + -1h = 2 + -1 Combine like terms: 1 + -1 = 0 0 + -1h = 2 + -1 -1h = 2 + -1 Combine like terms: 2 + -1 = 1 -1h = 1 Divide each side by '-1'. h = -1 Simplifying h = -1
| X+(.0825x)=30000 | | 2.562x=-12.32322 | | 4x=-3+y | | 5(3x-5)=-85 | | 220-2.75y+3.75y=245 | | 8m^4/m^4n^4 | | 7x+3y-3x+y= | | h+1=5h+-3+2 | | 3(x+2)=-5-3(x-3) | | X(x+2)-x-30=0 | | x+37=-123 | | 1128/188 | | 4a+1+-1a=19 | | 8xy^0/4y^5 | | 8x-6+x-1x-4x= | | 1/2(8g-20)=2(g-1)-3 | | -7(3x-8)=-49 | | 4a+1-a=-42 | | 10+.6n=.3n | | 5w-6-8w=2+7-3w | | -4=3w+5 | | 3x(x+5)-11=9x+12x+1 | | 12y=1/10 | | Q-7=23 | | 3x*x-6x-24= | | -20=-8+3v | | 2(3n+4)-2(2n-5)= | | 3/2-11x/9=-1/6 | | 2=k(x*2) | | 13.5+3.5y=6.5 | | 3(w-60)=30 | | (2m-5)(3m+6)=(6m-5)(m+4) |